2021
DOI: 10.1002/cpe.6531
|View full text |Cite
|
Sign up to set email alerts
|

Web service selection and composition based on uncertain quality of service

Abstract: Web services are becoming a major utility for accomplishing complex tasks over the Internet. In practice, the end‐users usually search for Web service compositions that best meet the quality of service (QoS) requirements (i.e., QoS global constraints). Since the number of services is constantly increasing and their respective QoS is inherently uncertain (due to environmental conditions), the task of selecting optimal compositions becomes more challenging. To tackle this problem, we propose a heuristic based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Finally, an improved version of NSGA-II was used to derive the non-dominated service compositions. The framework proposed in [38] involved two steps: the first one retains the pertinent services of the local tasks using majority grades, and the second step performs a constraint programming search to keep the optimal compositions. In the same line of thought, the work by [39] proposed a heuristic for filtering the desirable services of each local task using hesitant fuzzy sets and cross-entropy, then a metaheuristic termed grey wolf optimization was applied to retain the Top-K near-optimal service compositions.…”
Section: Service Selection With Uncertain Qosmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, an improved version of NSGA-II was used to derive the non-dominated service compositions. The framework proposed in [38] involved two steps: the first one retains the pertinent services of the local tasks using majority grades, and the second step performs a constraint programming search to keep the optimal compositions. In the same line of thought, the work by [39] proposed a heuristic for filtering the desirable services of each local task using hesitant fuzzy sets and cross-entropy, then a metaheuristic termed grey wolf optimization was applied to retain the Top-K near-optimal service compositions.…”
Section: Service Selection With Uncertain Qosmentioning
confidence: 99%
“…It is worth noting that the majority grade principle was initially presented by [45] for ranking the candidates of an election. After that, it was adapted by [38] to web service selection. According to Figure 7, we observed that all methods had almost the same CPU time up to n = 5.…”
Section: Experimental Studymentioning
confidence: 99%
“…Recent approaches have tackled uncertainty on the web using quality of service as an uncertainty modeling metric. The authors in Reference 14 proposed a heuristic based on majority judgment that aims to reduce the search space. Besides, in order to select the best top‐K compositions that respond to the QOS global constraints they performed a set of programming search.…”
Section: Related Workmentioning
confidence: 99%
“…Web services operate in dynamic network environments where factors such as network bandwidth, access point locations, and time can cause fluctuations in service performance, primarily reflected in the dynamic changes in QoS [6,7]. Even for the same user in the same network environment, uncertainties in server loads from service providers can lead to QoS fluctuations in Web services for different invocation times [8].…”
Section: Introductionmentioning
confidence: 99%